2005
DOI: 10.1590/s0037-86822005000500012
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos da ecologia e do comportamento de flebotomíneos em área endêmica de leishmaniose visceral, Minas Gerais

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
32
1
35

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 18 publications
6
32
1
35
Order By: Relevance
“…The predominance of L. longipalpis found in the present study showed to be in accordance with Missawa and Lima (2005) in the same municipality and other localities as reported by Oliveira et al (2003Oliveira et al ( , 2006 for Campo Grande, MS, Resende et al (2006) and Souza et al (2004) for Belo Horizonte, state of Minas Gerais (MG), Barata et al (2004Barata et al ( , 2005, and França- for Porteirinha, MG, Monteiro et al (2005) for Montes Claros, MG.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The predominance of L. longipalpis found in the present study showed to be in accordance with Missawa and Lima (2005) in the same municipality and other localities as reported by Oliveira et al (2003Oliveira et al ( , 2006 for Campo Grande, MS, Resende et al (2006) and Souza et al (2004) for Belo Horizonte, state of Minas Gerais (MG), Barata et al (2004Barata et al ( , 2005, and França- for Porteirinha, MG, Monteiro et al (2005) for Montes Claros, MG.…”
Section: Discussionsupporting
confidence: 92%
“…The closeness between the houses and the domestic animal shelters may account for the presence of insects indoors together with their capacity of endophilia. The high frequency of male insects found in both intra-and peridomiciliary areas has corroborated data provided by Oliveira et al (2003Oliveira et al ( , 2006, Resende et al (2006), Barata et al (2004Barata et al ( , 2005, evidencing the high adaptation capacity of sand flies enabling the disease transmission. The process of urbanization of insects and, consequently, of the disease is correlated with disorganized urban growth, followed by human migration from rural to urban regions and the environmental destruction.…”
Section: Discussionsupporting
confidence: 74%
“…La mayoría de los factores ambientales que afectan la epidemiología de varias leishmaniasis son aún pobremente entendidos o no se conocen muy bien (3,4). El estudio del comportamiento, de los hábitos alimentarios de Lutzomyia y de los factores que influyen sobre ellos resultan de gran importancia y contribuyen a la comprensión de la epidemiología de las leishmaniasis (4,5).…”
unclassified
“…These conditions were more pronounced in places like Alto do Moura and Nova Caruaru, where a higher frequency of sandfl ies was found. These environmental factors associated with low economic status of residents have been reported to contribute considerably to the transmission of VL (20) .…”
Section: Discussionmentioning
confidence: 99%
“…This species was collected in large numbers from chicken coops, pigsties, and corrals. In fact, it is known that chickens are among the preferred hosts for the blood meal of L. longipalpis (20) (26) .…”
Section: Discussionmentioning
confidence: 99%